PERANCANGAN PEMBANGUNAN INDONESIA MASA DESENTRALISASI - Robert Tua Siregar (JIP ( Jurnal Industri dan Perkotaan ), 2008)
The planing in Indonesia have a model changed, from top down model to bottom upmodel. It’s caused by economic crisis and recently situation. The asset in every region soimportant to be noticed with the program in order to succes. Planing model in desentralizationera make resource compatible with citizen participation who have similarity with DLA modelto decide region develovment executor. Participation of citizen position as user develovmentin region for welfare and sustainable develovment.